Immunogenicity of protein fractions of Pasteurella multocida in animals - Srivastava, S K (The Indian Journal of Animal Sciences, 2012)
Ammonium sulphate perceptible protein (PSAP) of Pasteurella multoeida serotype 6: B when fractionated using ion-exchange chromatography yielded 3 protein fractions, each eluted at sodium chloride gradient of 0.125 M (PASP-D), 0.25 M (PSAD-D I) and 0.35 M (PSAP-II). All the purified proteins along with PSAP adsorbed on sheep red blood cells and subsequently detected various levels of antibody titres in buffalo calves and rabbits, immunized with whole cell vaccine and later challenged with virulent P.multocida. Rabbits and mice given vaccines consisting of PSAP or PSAP-D I (major protein fraction) showed a similar level of protection against the challenge infection, as observed with the whole cell vaccinated group. Antisera from these immunized rabbits passively protected mice against P. multocida infection and exhibited moderate levels of bactericidal activity. Study suggested that the protein fraction from P. multicida could be used to develop a subunit vaccine against haemorrhagic septicaemia.